Expression of embryonic stem cell markers in keloid-associated lymphoid tissue. Issue 7 (30th March 2016) - Grant, Chelsea; Chudakova, Daria A; Itinteang, Tinte; Chibnall, Alice M; Brasch, Helen D; Davis, Paul F; Tan, Swee T
Abstract : Aims: To identify, characterise and localise the population of primitive cells in keloid scars (KS). Methods: 5-µm-thick formalin-fixed paraffin-embedded sections of KS samples from 10 patients underwent immunohistochemical (IHC) staining for the embryonic stem cell (ESC) markers OCT4, SOX2, pSTAT3 and NANOG, and keloid-associated lymphoid tissue (KALT) markers CD4 and CD20. NanoString gene expression analysis and in situ hybridisation (ISH) were used to determine the abundance and localisation of the mRNA for these ESC markers. Results: IHC staining revealed the expression of the ESC markers OCT4, SOX2, pSTAT3 and NANOG by a population of cells within KS tissue. These are localised to the endothelium of the microvessels within the KALTs. NanoString gene expression analysis confirmed the abundance of the transcriptional expression of the same ESC markers. ISH localised the expression of the ESC transcripts to the primitive endothelium in KS tissue. Conclusions: This report demonstrates the expression of ESC markers OCT4, SOX2, pSTAT3 and NANOG by the endothelium of the microvessels within the KALTs. These findings show a unique niche of primitive cells within KS, expressing ESC markers, revealing a potential therapeutic target in the treatment of KS.